PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SEKOLAH DASAR NEGERI 019 LOGAS - Murni, Atma; ', Yasmainar; ', Zuhri D (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :This study aims to improve the learning process and improvelearning outcomes math class V students of Elementary School 019 Logas in the secondsemester of the 2015/2016 school year by implementing cooperative learning modeltype Student Teams Achievement Divisions (STAD). The study consisted of two cycles,each cycle consisting of four phases: planning, implementation, observation, andreflection. Each end of the cycle carried out daily tests. Data collected throughobservation and tests in the form of daily tests. Observation is used to collect activitydata of teachers and students during the learning process, while tests are used to collectdata and mathematics learning outcomes will be provided in the form of daily tests. Theresults showed that the activity of teachers and students in learning has been consistentwith the planned implementation of learning. Most of the students to actively participatein the learning process is carried out, such as at the stage of delivering the goals andmotivation of students, the stage of presenting the information, organize students intostudy groups, guiding the group work and study presented the results of the workinggroup, responding to the presentation her friend, evaluate learning outcomes andreward. The results of this study indicate that the application of cooperative learningmodel STAD can improve the learning process and improve learning outcomes mathclass V students of Elementary School 019 Logas in the second semester of the schoolyear 2015/2016.Keywords : learning outcomes, Cooperative Learning, Student Teams Achievement Division(STAD), Action Research